(untitled) (South East Asia Journal of Public Health, 2019)
Bangladesh has made tremendous achievements in the health sector over the last few decades, albeit worse in maternal health (MH) compared to other South Asian countries. The fact that women, particularly poor, have less access to maternal health care (MHC) services is one of the prime reasons. The main objective of this study was to explore what types of barriers poor mothers faced during the service use. A triangulation of method (interviews of service recipients through interview schedule and service providers through checklist, focus group discussion and observation) was used for the collection of primary data (sample 200) from two slum areas in Rajshahi City between March and April, 2013. The study found socio-cultural and organizational barriers to access to MHC services more acute than physical and financial barriers. As suggested, building awareness of bad consequences of early marriage on MH, ensuring a strong coordination among service providing organizations in dispensing free drugs and posting female doctors in study areas are urgently needed for further improvement of MH. South East Asia Journal of Public Health Vol.8(1) 2018: 22-31